“We were having a lot of fun at the photographers”: Hellmuth Ladies’ College Students in Photographs, London, Ontario, 1885-1891 - Bell, Amy (Ontario History)

(untitled) (The Ontario Historical Society, 2015)
This article uses the photographic examples from a small female college to explore the use of photography as a social practice in late Victorian female colleges. It argues that photographs of students worked as both frames and surfaces: framing the visual details of their daily lives, while simultaneously allowing them a surface on which to fashion self-portraits. The photographs of Hellmuth Ladies’ College demonstrate the multiple arenas of late Victorian educational experience, the idealistic and aesthetic links between female educational institutions in the circum-Atlantic World, and the importance of school photographs to Canada’s photographic history.